URGENSI KURIKULUM PENDIDIKAN AGAMA ISLAM DALAM FENOMENA RADIKALISME DI INDONESIA - Muhammad Nur Adnan Saputra; Muhammad Nurul Mubin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2021)
The phenomenon of radicalism in Indonesia has recently become increasingly commonplace, there are many intolerant activities taking place in various layers of society. In particular, the radicalism carried out by elements who divide the ummah from the Islamic group, has made the image of Islam as a religion of peace for all nature and incompatible with a tolerant and moderate Islamic person. Not to mention that the understanding of intolerance has begun to be detected in educational institutions, many educational institutions are infiltrated with radical and intolerant views. Therefore, this study wants to describe how urgent the deradicalization program is in the curriculum in Indonesia. How is the concept of deradicalization in the curriculum, and how to deradicalise the existing curriculum in Indonesia. This study aims to determine the concept of deradicalization in the curriculum, as well as how to deradicalise existing curricula in Indonesia. The research method uses literature studies by collecting data from documents using descriptive-analysis methods. Deradicalization of the curriculum in Indonesia is very depleted, deradicalization in education can be carried out with a pedagogical approach through careful planning in the curriculum for learning Islamic religious education. In Indonesia, the government has begun to promote curriculum deradicalization with the Strengthening Character Education